Understanding the Structure of Reversible Coordination Polymers Based on Europium in Electrostatic Assemblies Using Time-Resolved Luminescence - Xu, Limin (Langmuir : the ACS journal of surfaces and colloids, 2016)
In situ characterization of the structure of reversible coordination polymers remains a challenge because of their dynamic and concentration-responsive nature. It is especially difficult to determine these structures in their self-assemblies where their degree of polymerization responds to the local concentration. In this paper, we report on the structure of reversible lanthanide coordination polymers in electrostatic assemblies using time-resolved luminescence (TRL) measurement. The reversible coordinating system is composed of the bifunctional ligand 1,11-bis(2,6-dicarboxypyridin-4-yloxy)-3,6,9-trioxaundecane (L2EO4) and europium ion Eu(3+). Upon mixing with the positively charged diblock copolymer poly(2-vinylpyridine)-b-poly(ethylene oxide) (P2VP41-b-PEO205), electrostatic polyion micelles are formed and the negatively charged L2EO4-Eu coordination complex simultaneously transforms into coordination "polymers" in the micellar core. By virtue of the water-sensitive luminescence of Eu(3+), we are able to obtain the structural information of the L2EO4-Eu coordination polymers before and after the formation of polyion micelles. Upon analyzing the fluorescence decay curves of Eu(3+) before and after micellization, the fraction of Eu(3+) fully coordinated with L2EO4 is found to increase from 32 to 83%, which verifies the occurrence of chain extension of the L2EO4-Eu coordination polymers in the micellar core. Our work provides a qualitative picture for the structure change of reversible coordination polymers, which allows us to look into these "invisible" structures